Consumers' WTP for certified traceable tea in China. Issue 5 (5th May 2015) - Liu, Xiaolin; Xu, Lingling; Zhu, Dian; Wu, Linhai
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine consumer attitudes toward and willingness to pay (WTP) for traceability of tea in China. Design/methodology/approach – The authors used the payment card method to elicit WTP for certified traceable tea and logistic regression model to analyze the factors that affected consumers' WTP. Findings – The results revealed that most consumers in China were concerned over tea safety; however, their WTP for certified traceable tea was limited. Only income and the degree of concern over tea safety affected the consumer's WTP for certified traceable tea greatly. When it came to consumers' WTP a positive price premium, income level, education, and attitude toward traceability of tea significantly influenced the actual premium consumers were willing to pay. Practical implications – The Chinese government and tea producers should pay attention when implementing tea traceability system. First, raising the consumers' income contributes to the premiums that consumers are willing to pay for certified traceable tea. Second, social groups, consumer organizations and tea producers should popularize knowledge of tea traceability. Third, given the low price premiums that consumers are willing to pay, the establishment of viable traceability of tea in China requires the producers and the government to bear some of the cost associated with the implementation of this system. Originality/value – In past studies on WTP for certified traceable food, the study is focussed on meat in developed countries, and the research has expanded range of study, by conducting a survey in China to determine consumers' WTP for certified traceable tea, and by empirically examining the main factors that influence the willingness of consumers to pay a price premium for certified traceable tea, as well as the premium that these consumers are willing to pay.